Assessing Effect of Marker-Based Improvement of Maize Synthetics on Agronomic Performance, Carotenoid Content, Combining Ability and Heterosis - Innocent Iseghohi (Agronomy, 2020)
Vitamin A deficiency (VAD) is a serious problem in sub-Saharan Africa (SSA) and other parts of the world. Understanding the effect of marker-based improvement (MARS) of two maize synthetics (HGA and HGB) representing different heterotic groups on their agronomic performance, carotenoid content, and combining abilities could help identify suitable sources to develop divergent inbred lines for optimizing heterosis. This study involved three selection cycles each of the two synthetics and their nine varietal-cross hybrids together with a released check variety was conducted across four diverse locations in Nigeria in 2018 and 2019. Environment and hybrid effects were significant on grain yield and other agronomic traits as well as provitamin A content and other carotenoids. Genetic improvement per cycle of MARS in the parental synthetics was 15% for provitamin A, 25% for β-carotene and 26% for lutein in HGA and 4% for grain yield, 3% for zeaxanthin and 5% for α-carotene in HGB. Grain yield and agronomic traits of the two maize synthetics were controlled by additive and non-additive gene effects, while provitamin A content and other carotenoids were mainly controlled by additive gene effects. Some selection cycles which were high in grain yield and provitamin A content were identified as potential sources of new and divergent maize inbred lines in maize breeding programs. Some varietal-cross hybrids expressed significant mid-parent heterosis for grain yield and moderate mid-parent heterosis for provitamin A, β-carotene and xanthophylls. These hybrids could be commercialized at reasonable prices to small-scale farmers in rural areas that are most affected by vitamin A deficiency.